Meningkatkan Kemampuan Berpikir Kritis Matematis Mahasiswa Menggunakan Model Pembelajaran Connected Mathematics Project (CMP) - Bayu Putra Irawan; Mirliani Mirliani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This research aims to; (1) knowing the implementation of class actions using Connected Mathematics Project (CMP) learning; (2) knowing student activities in Connected Mathematics Project (CMP) learning; (3) find out whether Connected Mathematics Project (CMP) learning can improve mathematical critical thinking skills of second semester students of Mechanical Engineering at the Raflesia Polytechnic. This type of research is Classroom Action Research with four stages including: Action planning → action implementation → observation → reflection. The subjects of this study were students of the second semester of the Polytechnic, totaling 30 people. Data collection using observation sheets and test sheets. The results showed that the implementation of classroom action with the Connected Mathematics Project (CMP) learning was carried out well, marked by an increase in student learning activities which was offset by a decrease in activities carried out by the teacher so that effective student learning was obtained. Students' mathematical critical thinking ability increases can be seen from the results of the tests given, if in the pre-test results only 5 students reached the good category, then the post-test results as many as 26 students have reached the good category, with 3 indicators, namely identifying problems , generalize and analyze the algorithm has reached a good category, for indicators of solving problems in the category enough. In conclusion, learning using the Connected Mathematics Project (CMP) method for second semester students of Mechanical Engineering at the Raflesia Polytechnic is effective in improving student mathematics learning outcomes. Keywords: Connected Mathematics Project (CMP), Critical Thinking, Ability Improvement